MEMBANGUN SISTEM PERIZINAN TERPADU BIDANG LINGKUNGAN HIDUP DI INDONESIA - Helmi, Helmi (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Applicability of Law. 32 of 2009 on the Protection and Management of the Environment an integrated licensing increasingly strict environmental field. Nevertheless, there are still many problems to the implementation of an integrated licensing is the inconsistency of the sectoral rules, ego-sectoral technical agencies, the strong economic interests than the interests of environmental protectionand social welfare. Implementation of an integrated licensing system requires integration of the environmental field of governance, institutions, power, mechanisms and requirements to achieve sustainable environmental management. That requires the synchronization settings, the integration of sustainable development and institutional models of integrated environmental permit system. Key words: environment, licensing system, integrated.